A number theory problem by A Former Brilliant Member

m and n are positive integers:

m ( m + 1 ) ( m + 2 ) ( m + 3 ) = n ( n + 1 ) m(m+1)(m+2)(m+3)=n(n+1)

Which statemants can be true?

39<m,n<1870 There are 2 solutions There is no solution There is only one solution There are many solutions 0<m,n<39 m and n must be bigger than 1870

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Cantdo Math
Apr 20, 2020

substitute m 2 + 3 m = x m^2+3m=x .Then, x(x+2)=n(n+1).

Here, if x>n then LHS >RHS.n=x doesn't work.Again if n>x then n+1>x+1 and consequently n+1 x + 2 \ge x+2 ,which implies RHS>LHS.

So,either way we get a contradiction.

This is brilliant. In my solution i wrote that, but I overcomplicated this.

x n = n + 1 x + 2 \frac{x}{n}=\frac{n+1}{x+2}

  • If x=n it isn't work.

  • If x>n x n > 1 \frac{x}{n}>1 and n + 1 x + 2 < 1 \frac{n+1}{x+2}<1 . It isn't good too.

  • If x<n x n < 1 \frac{x}{n}<1 and n + 1 x + 2 > 1 \frac{n+1}{x+2}>1 except x = n 1 x=n-1 , but if it is true: n + 1 x + 2 = 1 \frac{n+1}{x+2}=1 . So it's not good.

A Former Brilliant Member - 1 year, 1 month ago
Joseph Newton
Apr 18, 2020

Consider the numbers m ( m + 3 ) m(m+3) and ( m + 1 ) ( m + 2 ) (m+1)(m+2) , which multiply to give m ( m + 1 ) ( m + 2 ) ( m + 3 ) m(m+1)(m+2)(m+3) . For example, 6 × 7 × 8 × 9 = 3024 = ( 6 × 9 ) ( 7 × 8 ) = 54 × 56 6\times7\times8\times9=3024=(6\times9)(7\times8)=54\times56 Notice that the difference between these two numbers is 2 2 . This is in fact true for any value of m m : ( m + 1 ) ( m + 2 ) m ( m + 3 ) = m 2 + 3 m + 2 m 2 3 m = 2 (m+1)(m+2)-m(m+3)=m^2+3m+2-m^2-3m=2 Call these two numbers n n and k k . If we want n k nk to equal a fixed number, in this case m ( m + 1 ) ( m + 2 ) ( m + 3 ) m(m+1)(m+2)(m+3) , then if we increase n n we must decrease k k , and vice versa.

We currently have k = n + 2 k=n+2 , So, in order to have k = n + 1 k=n+1 , we have to increase n n and decrease k k . But, there is no way to do this while keeping n n and k k as integers and having n < k n<k , so it is not possible to achieve the required result.

Hence, given a positive integer m m it is impossible to find a positive integer n n so that m ( m + 1 ) ( m + 2 ) ( m + 3 ) = n ( n + 1 ) m(m+1)(m+2)(m+3)=n(n+1) .

m ( m + 1 ) ( m + 2 ) ( m + 3 ) = n ( n + 1 ) m(m+1)(m+2)(m+3)=n(n+1)

( m 2 + m ) ( m 2 + 5 m + 6 ) = n 2 + n (m^2+m)(m^2+5m+6)=n^2+n

m 4 + 5 m 3 + 6 m 2 + m 3 + 5 m 2 + 6 m = n 2 + n m^4+5m^3+6m^2+m^3+5m^2+6m=n^2+n

Add one to each side:

m 4 + 6 m 3 + 11 m 2 + 6 m + 1 = n 2 + n + 1 m^4+6m^3+11m^2+6m+1=n^2+n+1

Formulas: a 2 + 2 a b + b 2 = ( a + b ) 2 a^2+2ab+b^2=(a+b)^2 and a ( b ) + c ( b ) = b ( a + c ) a(b)+c(b)=b(a+c)

[ m 4 + 6 m 3 + 9 m 2 ] + [ 2 m 2 + 6 m ] + 1 = n 2 + n + 1 [m^4+6m^3+9m^2]+[2m^2+6m]+1=n^2+n+1

[ ( m 2 + 3 m ) 2 + 2 ( m 2 + 3 m ) ] + 1 = n 2 + n + 1 [(m^2+3m)^2+2(m^2+3m)]+1=n^2+n+1

( m 2 + 3 m ) ( m 2 + 3 m + [ 2 ] ) + 1 = n 2 + n + 1 (m^2+3m)(m^2+3m+[2])+1=n^2+n+1

( m 2 + 3 m ) ( m 2 + 3 m + 1 ) + m 2 + 3 m + 1 = n 2 + n + 1 (m^2+3m)(m^2+3m+1)+m^2+3m+1=n^2+n+1

( m 2 + 3 m + 1 ) ( m 2 + 3 m + 1 ) = n 2 + n + 1 (m^2+3m+1)(m^2+3m+1)=n^2+n+1

Now we know that:

n 2 < n 2 + n + 1 < n 2 + 2 n + 1 n^2< n^2+n+1 <n^2+2n+1

n 2 < n 2 + n + 1 < ( n + 1 ) 2 n^2< n^2+n+1 <(n+1)^2

So:

n 2 < ( m 2 + 3 m + 1 ) 2 < ( n + 1 ) 2 n^2< (m^2+3m+1)^2 <(n+1)^2

But in this interval there is no integer square.

There is no solution

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...